ANALISIS TINGKAT TOKSISITAS LIMBAH PEWARNAAN JEANS MENGGUNAKAN IKAN NILA (Oreochromis niloticus) - Caroline, Jenny; Rachmanu Eko Handriyono; Sonia S. Ximenes; Kusuma, Maritha Nilam (Journal of Research and Technology, 2019)
Jeans dyeing is one of the large or small scale industries that produces liquid waste from the coloring process. Liquid waste that enters the water will cause environmental pollution. It is necessary to study about the nature and characteristics of jeans dye wastewater through the toxicity test that refers to USEPA (2000) and OECD (2004) standards. Tests carried out by entering the concentration of certain wastewater in 5 (five) reactors with tilapia fish (Oreochromis niloticus) biota. Preliminary research conducted in 7 day acclimation process and 1 day range finding test. Running process carried out for 96 hours for fish 5 cm. The analysis was carried out every 24th, 48th, 72th and 96th hour for analysis of temperature, pH, DO, and mortality. Heavy metal (Cr) analysis was carried out in fish bodies and wastewater at each concentration. The initial characteristics of jeans stained liquid waste for pH: 7, temperature: 30, 7ºC, DO: 8.5 mg/l, TSS: 1040.0 mg/l; BOD: 137 mg/l; COD: 484.8 mg/l and Total chrome: 3.079 mg/l. The level of LC50 toxicity concentration in tilapia fish fish 5 cm size of 12.59% results obtained from the calculation of probit with excel software. The content of chrome total (Cr) contained in the test biota for 96 hours ranged from 1.03 l/kg to 1.93 l/kg.